Internal structure of matrix-type multilayer capsules templated on porous vaterite CaCO3 crystals as probed by staining with a fluorescence dye - Jeannot, Lucas; Bell, Michael; Ashwell, Ryan; Volodkin, Dmitry; Vikulina, Anna S. (Micromachines, 2018)
Multilayer capsules templated on decomposable vaterite CaCO3 crystals are widely used as vehicles for drug delivery. The capsule represents typically not a hollow but matrix-like structure due to polymer diffusion into the porous crystals during multilayer deposition. The capsule formation mechanism is not well-studied but its understanding is crucial to tune capsule structure for a proper drug release performance. This study proposes new approach to noninvasively probe and adjust internal capsule structure. Polymer capsules made of poly(styrene-sulfonate) (PSS) and poly(diallyldimethylammonium chloride) (PDAD) have been stained with fluorescence dye rhodamine 6G. Physical-chemical aspects of intermolecular interactions required to validate the approach and adjust capsule structure are addressed. The capsules consist of a defined shell (typically 0.5-2 μm) and an internal matrix of PSS-PDAD complex (typically 10-40% of a total capsule volume). An increase of ionic strength and polymer deposition time leads to the thickening of the capsule shell and formation of a denser internal matrix, respectively. This is explained by effects of a polymer conformation and limitations in polymer diffusion through the crystal pores. We believe that the design of the capsules with desired internal structure will allow achieving effective encapsulation and controlled/programmed release of bioactives for advanced drug delivery applications.
CRIS-Team Scopus Importer:2021-06-08
Keywords: Calcium carbonate; Fluorescence; Layer-by-layer; Mesoporous; Self-assembly